2015
DOI: 10.3892/etm.2015.2694
|View full text |Cite
|
Sign up to set email alerts
|

Anti-mitochondrial M2 antibody-positive autoimmune hepatitis

Abstract: Abstract. Anti-mitochondrial M2 antibody (AMA-M2) is specific to primary biliary cirrhosis (PBC), but can also be found in certain patients with autoimmune hepatitis (AIH). Effective methods of differentiating between PBC and AIH are required, as their clinical course and management are different. Titers of AMA-M2 were analyzed before and after follow-up in patients with PBC or AIH. Patients who underwent liver biopsy and were diagnosed with either AIH (10 patients) or PBC (3 patients) were enrolled in the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…These findings are consistent with the known idea that centrilobular necrosis can be the only pathologic feature in up to 2-3% of patients presenting with AIH flares [11][12][13]. Moreover, the patient had positive antimitochondrial antibodies, which, while being more specific for primary biliary cholangitis, might be associated with AIH [14]. In these ALF cases, liver support systems were not used, since they were unavailable.…”
Section: Discussionsupporting
confidence: 74%
“…These findings are consistent with the known idea that centrilobular necrosis can be the only pathologic feature in up to 2-3% of patients presenting with AIH flares [11][12][13]. Moreover, the patient had positive antimitochondrial antibodies, which, while being more specific for primary biliary cholangitis, might be associated with AIH [14]. In these ALF cases, liver support systems were not used, since they were unavailable.…”
Section: Discussionsupporting
confidence: 74%
“…The non-classical clinical phenotypes of AIH, particularly AMA-positive AIH, should be distinguished from PBC. In general, AMAs-M2 antibody is specific to PBC patients, but may also be occasionally discovered in certain AIH patients[146]. Efficient means of discriminating between AIH and PBC are required, due to the fact that their clinical process and treatment are disparate[146].…”
Section: Differential Diagnosis Of Pbcmentioning
confidence: 99%
“…In general, AMAs-M2 antibody is specific to PBC patients, but may also be occasionally discovered in certain AIH patients[146]. Efficient means of discriminating between AIH and PBC are required, due to the fact that their clinical process and treatment are disparate[146]. One recent study has shown that antibodies to filamentous-actin (anti-F-actin) protein can not only be considered the serological marker of type 1 AIH, but may also predict AIH recurrence[147].…”
Section: Differential Diagnosis Of Pbcmentioning
confidence: 99%
See 2 more Smart Citations